Diagnostic and Therapeutic Strategies for Acute Intracranial Atherosclerosis-related Occlusions - Lee, Jin Soo; Hong, Ji Man; Kim, Jong S. (Journal of stroke, 2017)
Intracranial atherosclerosis-related occlusion (ICAS-O) is frequently encountered at the time of endovascular revascularization treatment (ERT), especially in Asian countries. However, because baseline angiographic findings are similar between ICAS-O and embolism-related occlusion (EMB-O), it is difficult to differentiate the etiologies before the ERT procedure. Moreover, despite successful randomized trials on ERT, results from studies examining the optimal treatment protocol in ICAS-O patients remain unclear. In this review, we describe the clinical and imaging factors that may possibly differentiate ICAS-O from EMB-O. We will also discuss some current hurdles for treating ICAS-O in the hyperacute period and suggest the optimal ERT strategy for ICAS-O patients.